Molecular and clinical heterogeneity within MYC-family amplified medulloblastoma is associated with survival outcomes: a multicenter cohort study - Schwalbe, Edward C.; Lindsey, Janet C.; Danilenko, Marina; Hill, Rebecca M.; Crosier, Stephen; Ryan, Sarra; Williamson, Daniel; Castle, Jemma; Hicks, Debbie; Kool, Marcel; Milde, Till; Korshunov, Andrey; et al. (Neuro-Oncology, 2025)
MYC/MYCN are the most frequent oncogene amplifications in medulloblastoma (MB) and its primary biomarkers of high-risk (HR) disease. However, while many patients’ MYC(N)-amplified tumors are treatment-refractory, some achieve long-term survival. We therefore investigated clinicobiological heterogeneity within MYC(N)-amplified MB and determined its relevance for improved disease management.We characterized the clinical and molecular correlates of MYC- (MYC-MB; n = 64) and MYCN-amplified MBs (MYCN-MB; n = 95), drawn from >1600 diagnostic cases.Most MYC-MBs were molecular group 3 (46/58; 79% assessable) and aged ≥3 years at diagnosis (44/64 [69%]). We identified a “canonical” very high-risk (VHR) MYC-amplified group (n = 51/62; 82%) with dismal survival irrespective of treatment (11% 5-year progression-free survival [PFS]), defined by co-occurrence with ≥1 additional established risk factor(s) (subtotal surgical-resection [STR], metastatic disease, LCA pathology), and commonly group 3/4 subgroup 2 with a high proportion of amplified cells. The majority of remaining noncanonical MYC-MBs survived (i.e. non-group 3/group 3 without other risk features; 11/62 (18%); 61% 5-year PFS). MYCN survival was primarily related to molecular group; MYCN-amplified SHH MB, and group 3/4 MB with additional risk factors, respectively defined VHR and HR groups (VHR, 39% [35/89]; 20% 5-year PFS/HR, 33% [29/89]; 46% 5-year PFS). Twenty-two out of 35 assessable MYCN-amplified SHH tumors harbored TP53 mutations; 9/12 (75%) with data were germline. MYCN-amplified group 3/4 MB with no other risk factors (28%; 25/89) had 70% 5-year PFS.MYC(N)-amplified MB displays significant clinicobiological heterogeneity. Diagnostics incorporating molecular groups, subgroups, and clinical factors enable their risk assessment. VHR “canonical” MYC tumors are essentially incurable and SHH-MYCN-amplified MBs fare extremely poorly (20% survival at 5 years); both require urgent development of alternative treatment strategies. Conventional risk-adapted therapies are appropriate for more responsive groups, such as noncanonical MYC and non-SHH-MYCN MB.
Online verfügbar: 08. Oktober 2024
Gesehen am 16.04.2025